Społeczeństwo obywatelskie a moralność - Gałkowski, Jerzy W.; Kanafa, Łukasz (Annales. Etyka w Życiu Gospodarczym, 2010)
Civil society was defined in various ways. Among others, J. Locke, G.W.F. Hegel and A. de Tockeville presented the most relevant characteristic of what civil society is or could be. For the purpose of the paper we distinct civil society and the state. To the first one we assign spontaneity and diversity, the second we treat as procedural and homogeneous. In the paper we will stand for the thesis: civil society is the nest of virtues and as such characterized plays one of the most prominent parts in contemporary social and political reality. The problem is not that presently civil society does not exist. The problem is that once it was established within the state, it has been developed in such a way that it became a hybrid combined from the state and what could be called apolitical human activity. The core of the problem is that the hybrid is more political than apolitical. To the essence of civil society belong: existence of free associations of any kind, economy free from political coerce as much as it could be and public sphere of opinion, all organized in such a political way that the political power is limited by division of it to three independent institutions: a legislature, an executive and a judiciary and also by the law. A ground for apolitical human social activities was prepared by J. Locke in his political theory. The state is one of possible emanations of apolitical society in the state of nature. Montesquieu expanded such a vision of society that it exists within the state but the state itself is limited by division of political power and civil rights which allow the members of the society to protect their freedom and dignity. Moral civil society we are developing protect the citizens from overwhelming influence of the state and particular egoisms of individuals. As such it promotes moral activity, it brings trust to the public sphere and it protects human dignity.